The Oxford handbook of Ezekiel - Carvalho, Corrine 1958- (Oxford Oxford University Press, Incorporated, 2023)
The Oxford Handbook of Ezekiel provides introductions to the major trends in the scholarship of Ezekiel, one of the Bible's most debated books, from many of the leading scholars in the field. After an introductory overview of these trends, each essay discusses an important element in the scholarly engagement with the book. Several essays discuss the history of the text (e.g., historical context, redactional layers, text criticism, use of other Israelite and near eastern traditions). Others focus on key themes in the book (e.g., temple, priesthood, law, politics), while still others look at the book's reception history and contextual interpretations (e.g., art, Christian use, gender approaches, postcolonial approaches, trauma theory). Taken together, these essays demonstrate the vibrancy of Ezekiel research in the twenty-first century.
Intro -- Title Page -- Copyright Page -- Contents -- Acknowledgments -- Contributors -- 1. Ezekiel Scholarship in the Twenty-first Century -- 2. Ezekiel in Its Historical Context -- 3. The Mesopotamian Context of Ezekiel -- 4. Ezekiel and Israel's Legal Traditions -- 5. Ezekiel among the Prophetic Tradition -- 6. Ezekiel and Israelite Literary Traditions -- 7. Text-Critical Issues in Ezekiel -- 8. Rhetorical Strategies in the Book of Ezekiel -- 9. Ezekiel as a Written Text: Archiving Visions, Remembering Futures -- 10. Ezekiel among the Exiles -- 11. Ezekiel and Politics -- 12. Priests, Levites, and the Nasi: New Roles in Ezekiel's Future Temple -- 13. Ezekiel's Concept of Covenant -- 14. Ezekiel and the Foreign Nations -- 15. Ezekiel and the Priestly Traditions -- 16. Communications of the Book of Ezekiel: From the Iron Wall to the Voice in the Air -- 17. Ezekiel in Christian Interpretation: Gog, Magog, and Apocalyptic Politics -- 18. Pastoral Appropriations of Ezekiel -- 19. Ezekiel in the Jewish Tradition -- 20. Where There's Fire There's Smoke: Text and Image in the Ezekiel Painting at Dura-Europos -- 21. Ezekiel and Gender -- 22. Embodiment in Ezekiel -- 23. Ezekiel as Trauma Literature -- 24. Uncertainties in First Contact? Ezekiel's Struggle Toward a "Comparative Gaze" -- 25. Ezekiel's Map of Future Past -- 26. Ezekiel Imperialized Geographies in the Nation Oracles -- 27. Ezekiel's Tangible Ethics: Physicality in the Moral Rhetoric of Ezekiel -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung